2018
DOI: 10.1002/cyto.b.21722
|View full text |Cite
|
Sign up to set email alerts
|

CD200 is a useful marker in the diagnosis of chronic lymphocytic leukemia

Abstract: Background The diagnosis of CLL is supported by a typical morphology and immunophenotype and usually does not present difficulties. Nevertheless, some patients with CLL can show an atypical phenotype, this raising the possibility of a lymphoproliferative disorder other than CLL. It has been recently shown that the expression of CD200 could be a rather consistent marker for CLL. Methods The expression of CD200 was investigated in 120 consecutive patients with B‐cell chronic lymphoproliferative disorders (B‐CLPD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 35 publications
(72 reference statements)
4
16
1
Order By: Relevance
“…CD200 was highly informative in the differential diagnosis between CLL and mantle cell lymphoma; 95% of CLL patients were found to be CD200 positive while only 8% of mantle cell patient were CD200 positive. This agrees with other studies of CLL which have generally shown positivity rates for CD200 above 97% and almost universal negativity in mantle cell lymphoma (17,18). In other lymphoproliferative disorders, however they found CD200 to be suboptimal in the differential diagnosis.…”
supporting
confidence: 92%
“…CD200 was highly informative in the differential diagnosis between CLL and mantle cell lymphoma; 95% of CLL patients were found to be CD200 positive while only 8% of mantle cell patient were CD200 positive. This agrees with other studies of CLL which have generally shown positivity rates for CD200 above 97% and almost universal negativity in mantle cell lymphoma (17,18). In other lymphoproliferative disorders, however they found CD200 to be suboptimal in the differential diagnosis.…”
supporting
confidence: 92%
“…Forty‐three articles and meeting abstracts (Alapat et al, ; Arlindo, Marcondes, Fernandes, & Faulhaber, ; Aytan et al, ; Brunetti et al, ; Challagundla, Medeiros, Kanagal‐Shamanna, Miranda, & Jorgensen, ; D'Arena et al, ; Debord et al, ; Dorfman & Shahsafaei, ; El Desoukey, Afify, Amin, & Mohammed, ; El Din Fouad, Ibrahim, Abdel Aziz, & Ibrahim, ; Espinet et al, ; Falay et al, ; Fan et al, ; Fanoni et al, ; Favre et al, ; Hu et al, ; Köhnke et al, ; Lesesve et al, ; Mason, Pozdnyakova, Li, Dudley, & Dorfman, ; Miao et al, ; Miguet et al, ; Mongeau‐Marceau et al, ; Montesdeoca et al, ; Mora et al, ; Palumbo et al, ; Pillai et al, ; Poongodi, Varma, Naseem, Parveen, & Varma, ; Rahman et al, ; Rahman, Kumar, Gupta, Singh, & Nityanand, ; Rawstron et al, ; Rawstron et al, ; Rawstron et al, ; Sallam, Elsalakawy, El‐Sewefy, & Khattab, ; Sandes et al, ; Sorigue, Franch‐Sarto, Sarrate, & Junca, ; Sorigue, Juncà, et al, ; Sorigue, Junca, & Granada, ; Sorigue, Raya, et al, ; Spacek et al, ; Starostka et al, ; Ting et al, ; van Dongen et al, ; Ye et al, ) were read in full, of which 16 were excluded (Figure S1). Therefore, 27 studies (5,764 patients) were included.…”
Section: Resultsmentioning
confidence: 99%
“…However, one study that used a higher fluorescence cutoff reported a suboptimal sensitivity for CLL (Lesesve et al, ). Similarly, two further studies (Fan et al, ; Mora et al, ) reported the necessary data to compare a standard threshold (any positivity) to a higher threshold. Both of them found a predictable loss of sensitivity and increase in specificity leading to a similar overall accuracy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Mora and colleagues studied 120 consecutive patients with chronic B‐lymphoproliferations (81 within the CLL spectrum and 39 with other monoclonal B‐cell disorders) to establish whether CD200, a member of the Ig receptors membrane proteins superfamily, would have added value to the immunological scoring system already developed by Matutes et al . CD200 had already been suggested to be rather specific for B‐CLL in earlier studies.…”
Section: Cd200 and Cd62l In B‐chronic Lymphocytic Leukemia (B‐cll)mentioning
confidence: 99%